A review on heavy metals accumulation in coastal bivalves used in seafood industry: guide to safely consumption of seafood. - Sethukali, A.; Weerasooriyagedara, M. S. (International Journal of Scientific and Research Publications, 2018)
Bivalve is one of the most nutritionally balanced seafood but is highly correlated with heavy metal toxicity and ultimately causing public health impacts. Several biological and geochemical factors are influencing the uptake and bioaccumulation of heavy metals in bivalves which leads to destroy aquatic ecosystem and becoming risk of food consumption. Cadmium, lead, copper, zinc and mercury are widely reported as trace metals bioaccumulation in bivalves due to industrial wastages and domestic discharges from urbanized areas. Though, a number of studies have performed to identify the presence of heavy metals in different bivalve species, limited researches have exclusively focused on relationship between nutritional composition and available heavy metals in different bivalve species with regards to safe human consumption.
Keywords: Bioaccumulation; Bivalve; Heavy metals; Seafood